2021
DOI: 10.1038/s41598-021-93227-3
|View full text |Cite
|
Sign up to set email alerts
|

A deep learning method for automatic segmentation of the bony orbit in MRI and CT images

Abstract: This paper proposes a fully automatic method to segment the inner boundary of the bony orbit in two different image modalities: magnetic resonance imaging (MRI) and computed tomography (CT). The method, based on a deep learning architecture, uses two fully convolutional neural networks in series followed by a graph-search method to generate a boundary for the orbit. When compared to human performance for segmentation of both CT and MRI data, the proposed method achieves high Dice coefficients on both orbit and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Firstly, the manual segmentation is performed by MRI experts, which is a tedious and complex task, but accurate, while the accurate and straightforward software does automatic segmentation due to developments in artificial intelligence. It is also worth mentioning that the MRI experts first label the datasets used for automatic segmentation ( 41 ). The evaluation metrics used for brain tumor segmentation are DSC, accuracy, sensitivity, and precision ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the manual segmentation is performed by MRI experts, which is a tedious and complex task, but accurate, while the accurate and straightforward software does automatic segmentation due to developments in artificial intelligence. It is also worth mentioning that the MRI experts first label the datasets used for automatic segmentation ( 41 ). The evaluation metrics used for brain tumor segmentation are DSC, accuracy, sensitivity, and precision ( 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…Orbital MRI examination is free of ionizing radiation damage and is superior in revealing soft tissue. Compared with MRI examinations, CT images are noisier (Hamwood et al, 2021). Therefore, the traditional UNet algorithm is better suited to training with CT images because it extracts rich feature scales and can effectively filter local noise (Pan et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AI can segment bony structures from orbital CT/MRI images. Hamwood et al (2021) developed a DL system for the segmentation of bony regions from orbital CT/MRI images that exhibited excellent efficiency, particularly in terms of computational time. Li et al (2022a) extracted bony orbit features and analyzed Asian aging characteristics through the popular deep CNN (DCNN) model.…”
Section: Sabatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various autosegmentation methods that have historically been applied to computed tomography (CT) images have shown promise on MRI [6], including deformable image registration (DIR)based structure propagation [4,7], atlas-based autosegmentation [8][9][10], and deep learning [11][12][13]. While several studies have shown that deep learning can improve organ-at-risk (OAR) segmentation accuracy compared to atlas-based autosegmentation on CT for head and neck [14][15][16] and other treatment sites [17][18][19][20], to our knowledge, only a single study thus far has directly compared these methods on MRI for any treatment site [21].…”
Section: Introductionmentioning
confidence: 99%